2020 Visionary Leader Ferlie Villacorte. Issue 1 (January 2021) - Ellis, Sharon
Abstract : The following manuscript is the winning 2020 Richard Hader Visionary Leader Award entry submitted to Nursing Management in recognition of Ferlie Villacorte, MPH, MSN, RN, CNS, clinical nursing director of ambulatory care services at Harbor-UCLA Medical Center in California. Abstract : Meet our newest winner, Ferlie Villacorte, MPH, MSN, RN, CNS, clinical nursing director of ambulatory care services at Harbor-UCLA Medical Center in California.